2016
DOI: 10.21776/ub.mnj.2016.002.01.3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Severe Head Injury Epidural Hematoma Trepanation Respond Time With Outcome

Abstract: Latar belakang. Hematoma epidural adalah perdarahan intrakranial yang terjadi karena fraktur tulang tengkorak akibat cedera kepala dimana terdapat akumulasi darah dalam rongga antara lapisan duramater dan tulang tengkorak. Tujuan. Untuk mengetahui hubungan antara respond time tindakan trepanasi hematoma epidural pada pasien cedera kepala berat dengan outcome. Metode. Penelitian observasional analitik retrospektif (cross sectional) dengan sampel 30 orang yang diambil di Rumah Sakit Saiful Anwar Malang periode J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…Based on age, it can be seen that most EDH patients are young adults (18-39 years). The results of this study are supported by previous studies which showed that the highest incidence of EDH cases occurred in the young adult age group of 20-30 years [3,12]. In accordance with the theory that states that adolescents and young adults are very susceptible to head injuries.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Based on age, it can be seen that most EDH patients are young adults (18-39 years). The results of this study are supported by previous studies which showed that the highest incidence of EDH cases occurred in the young adult age group of 20-30 years [3,12]. In accordance with the theory that states that adolescents and young adults are very susceptible to head injuries.…”
Section: Discussionsupporting
confidence: 91%
“…This is because this age group often performs activities that are at risk of causing head injuries because they are in the most active period of life [7]. Cases of EDH rarely occur at the age above 60 years, this is caused by old age anatomically, the attachment of the dura mater in the skull bones is getting stronger so it is difficult to provide a gathering place for epidural haemorrhage [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation